1993
DOI: 10.1002/pola.1993.080310518
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic polyesterification in organic media. Enzyme‐catalyzed synthesis of linear polyesters. I. Condensation polymerization of linear hydroxyesters. II. Ring‐opening polymerization of ϵ‐caprolactone

Abstract: SYNOPSISWith the object to synthesize polyesters by enzymatic catalysis in organic media, two directions have been investigated ( 1 ) the condensation polymerization of linear o-hydroxyesters and ( 2 ) the ring-opening polymerization of lactones. The commerciallyavailable crude porcine pancreatic lipase ( P P L ) , suspended in organic solvents, was the preferred enzyme for the reactions. In order to determine the optimal conditions for the condensation polymerization, the bifunctional methyl 6-hydroxyhexanoat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
206
0
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(213 citation statements)
references
References 18 publications
4
206
0
3
Order By: Relevance
“…Gutman et al (1987) reported the first study on polyester synthesis by enzyme-catalyzed polymerization of A-B type monomers. Two independent groups in 1993 (Knani et al, 1993;Uyama and Kobayashi, 1993) were first to report enzyme-catalyzed ring-opening polymerization (ROP). Their studies focused on 7-and 6-membered unsubstituted cyclic esters e-caprolactone and d-valerolactone, respectively.…”
Section: Enzymatic Polymerizationsmentioning
confidence: 99%
“…Gutman et al (1987) reported the first study on polyester synthesis by enzyme-catalyzed polymerization of A-B type monomers. Two independent groups in 1993 (Knani et al, 1993;Uyama and Kobayashi, 1993) were first to report enzyme-catalyzed ring-opening polymerization (ROP). Their studies focused on 7-and 6-membered unsubstituted cyclic esters e-caprolactone and d-valerolactone, respectively.…”
Section: Enzymatic Polymerizationsmentioning
confidence: 99%
“…21,22 According to their result, AB unit plays a key roll to make the chain grow. The enzyme-substrate complex (Enz-O-AB) is attacked by B, and then the oligomer consists of hydroxyl terminated products such as BAB, B(AB) 2 , B(AB) 3 , and so on. Finally they concluded that the preferred product is hydroxyl terminated one.…”
Section: Polycondensation With Equimolar Quantities Of Diacid and Diolmentioning
confidence: 99%
“…Lots of investigations on different ring size of lactones, solvent effect, and an enzymatic activity of lipases immobilized on different matrix have been carried out. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] In case of condensation of diol and diacid with aliphatic chain, the high molecular weight polyester can be obtained by removing a leaving group. Klibanov et al have explored the enzymatic catalyzed asymmetric polymerization of aliphatic diol and diacid.…”
mentioning
confidence: 99%
“…Of all available lipases, by far the most used in organic chemistry is Candida Antarctica Lipase B (CALB). Enzyme catalyzed lactones ROP in organic media have been conducted for the polymerizations of -caprolactone (-CL) [1,2]. Recently several researches have been carried out in this field from creating new biopolymers with the exisiting lipases to synthesizing biopolymers using newly developed enzymes.…”
Section: Introductionmentioning
confidence: 99%